Pengaruh PMA, PMDN, Ekspor, Belanja Pendidikan dan Belanja Kesehatan terhadap Pertumbuhan Ekonomi Di Provinsi dalam Pulau Sumatera - Nuri, Desi Rahma; Junaidi, Junaidi; Achmad, Erni (J-MAS (Jurnal Manajemen dan Sains), 2024)
This was a quantitative study. The data were secondary data from six Provinces in SumateraÂ  in the period 2010-2021 obtained from the BPS and DJPK. The data were panel data analysis using the fixed effect regression model processed by Eviews 12. The results of the study showed that: 1) foreign investment have significant positive effect on economic growth in Sumatera with a probability value of 0.0035. 2) domestic investment have significant positive effect on economic growth in Sumatera with a probability value of 0.0001. 3) Exports have no significant effect on economic growth on the island of Sumatra with a probability value of 0.08019. 4) Education spending has a positive and significant influence on economic growth on the island of Sumatra with a probability value of 0.0006. 5) Health expenditure has a positive and significant influence on economic growth on the island of Sumatra with a probability value of 0.0091. The R-squared value in this study is 0.986931, this means that the contribution of all independent variables in explaining the variable is 98.69%.